1990
DOI: 10.1007/bf03341850
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religion in Psychiatric Education: A National Survey

Abstract: Approximately 80% of the members of the American Association of Directors of Psychiatric Residency Training responded to a survey on the role of religion in psychiatric education. Survey results suggest that religious ideation by resident candidates is a relatively unimportant variable in the programs' selection; didactic instruction on any aspect of religion is infrequent; clinical supervision on religious dynamics is variable but more likely to occur than didactic instruction; and academic progression is rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…A growing body of research suggests that religion/spirituality may have a positive effect on coping and enhancing clinical outcomes 17–28. Attention to the patient's belief system and cultural background seems to be critical to a patient's healing process 10. In agreement with these findings, schools of medicine, nursing and other health professions have added, or are adding, curricula in areas such as religion, culture and spirituality 10.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A growing body of research suggests that religion/spirituality may have a positive effect on coping and enhancing clinical outcomes 17–28. Attention to the patient's belief system and cultural background seems to be critical to a patient's healing process 10. In agreement with these findings, schools of medicine, nursing and other health professions have added, or are adding, curricula in areas such as religion, culture and spirituality 10.…”
Section: Discussionmentioning
confidence: 89%
“…Attention to the patient's belief system and cultural background seems to be critical to a patient's healing process 10. In agreement with these findings, schools of medicine, nursing and other health professions have added, or are adding, curricula in areas such as religion, culture and spirituality 10. Psychiatry programmes around the US are slowly catching up and developing residency trainings that incorporate the cultural and spiritual dimension into residency curricula.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most counseling occurs in secular settings, such as colleges, universities, private practices, and human service agencies. Because religion and spirituality are not the main themes in these various settings, counselors may be reluctant to address these issues with the client (Kelly, 1994;Sansone, Khatain, & Rodenhauser, 1990;Shafranske & Malony, 1990). However, the spiritual aspect of a client should be addressed in the counseling process when appropriate (Chandler & Holden, 1992).…”
mentioning
confidence: 93%
“…A similar survey of 409 clinical psychologist m embers of the American Psychological Association revealed that only 5% had had religious or spiritual issues addressed in their professional training (Shafranske & Malony, 1990). Similarly, when the m embers of the Am erican Association of Directors of Psychiatric Residency Training were asked if their progra m had a course on any aspect of religion, 18.5% responded ª occasionally,º and 12% responded ª frequently or alwaysº (Sansone, Khatain, & Rodenhauser, 1990). The greater likelihood that mental health nurses are exposed to religious ±spiritual issues early in their professional training helps explain why they are m ore likely to recognize the roles of religion and spirituality in empirical research and clinical care.…”
Section: Discussionmentioning
confidence: 99%